Player and game characteristics and head impacts in female youth ice hockey players - Reed, N.; Taha, T.; Greenwald, R.; Keightley, M. (Journal of Athletic Training, 2017)
Context: Despite the growing popularity of ice hockey among female youth and interest in the biomechanics of head impacts in sport, the head impacts sustained by this population have yet to be characterized.